Player-aware resource compensation in interrupted cricket matches - Salam Zia; Hannan Bin Liaqat; Hafiz Usman Zia; Xiangjie Kong; Sultan Shamshad (PeerJ Computer Science, 2022)
The International Cricket Council (ICC) uses the Duckworth-Lewis-Stern (DLS) method for resource compensation in interrupted games, which is an upgraded version of the Duckworth-Lewis (D/L) method. In order to compensate resources, the D/L method uses a generic resource table for all teams without considering both teams’ past performance, venue of the match, and players participating in that match. That is why teams cannot strategize according to their strengths and play according to D/L’s requirements. This paper presents a method for Player-aware Resource Compensation in Interrupted Cricket Matches (PRCICM). The PRCICM model is dynamic because it allocates a different number of resources to different teams based on their resource usage in the past, players involved in the match and venue of the match. The proposed method eliminates the need to find the generalized scoring patterns with a player-driven approach. A team-specific approach is more appropriate because of teams’ different formations and playing approaches.